INSTRUMEN JARINGAN KOMPUTER UNTUK MAHASISWA PENDIDIKAN INFORMATIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA - Yuliatri Sastrawijaya; Muhammad F Duskarnaen; Hamidillah Ajie; Hana Amanda Putri; Khasanah Khasanah (Akademika, 2022)
Education is a learning effort for students with the intention of making people more critical in thinking. Measurement is a scoring procedure for special attributes or characteristics attached to a person associated with the attribute being measured. This study aims to produce a computer network instrument that has been validated by three lecturers, and has been validated and the differential power has been calculated with 200 student respondents and its reliability has been calculated. This research is an experimental research, the subjects of the research are students of the Informatics and Computer Engineering Education study program at Jakarta State University who are taking computer network courses. Based on the results of the analysis of computer network instruments for the category of material and face validity which were filled in by 3 lecturers, out of 50 items they were declared good and worthy of being tested on students. In the next step, 200 students who had passed the Computer Networks course were taken to be tested for validity to see the differentiability of the questions and the level of difficulty of the questions, the result was that there were 7 (14%) items including easy items with very good differentiating power, there were 38 items ( 76%) including moderate grains, with good discriminating power, and there are 5 items including difficult grains with sufficient discriminating power. The next step is that the results of the answers of the 200 students who were tested calculated the reliability and obtained good results of r = 0.82. From the results of this study, the finished instrument was given to students who took the Computer Networks course as many as 70 people.